Estimation of the Survival Rate of Pinus Sylvestris Urban Landscaping Facilities in the City of Krasnoyarsk. Issue 4 (March 2021) - Avdeeva, E; Panov, A
Abstract: Scotch pine takes an increasing place in urban greening. Its high decorative qualities, especially in winter, undemanding to soil conditions, rapidity of growth, winter hardiness, high sanitary and hygienic and environmental protection properties contribute to the greatest distribution. It has been established that when creating green spaces at city greening objects, it is necessary to take into account the dynamics of plant survival. The study of the survival rate of Scots pine according to the reaction of the growth of lateral branches showed that the main decrease in growth after transplantation occurs in the second year, the restoration of growth occurs after 7-8 years. The survival rate of plants largely depends on the state of the urban environment and the technology after planting care for plantings, especially in the first and second years after transplanting. At the same time, when creating green spaces, it is also necessary to comply with the recommendations of the "Building codes and regulations" in relation to the minimum distances to buildings, structures, footpaths and driveways, as well as the schedule of work to create a landscaping facility.